IMPACT TRAINING ON KNOWLEDGE DISSEMINATION ON TEACHING AND LEARNING IN MALAYSIAN HIGHER EDUCATION - Hussin, Hanipah; Sharimllah, Ramachanran; Mohd Pilus, Asiah; Dora, Mohd Taib (Journal of Human Capital Development (JHCD), 2010)
This research, grant by Akademi Kepimpinan Pengajian Tinggi Malaysia (AKEPT). The purpose of this paper is to reveal the impact of AKEPT Training Program on lecturers toward their contribution on knowledge dissemination processes among peers and colleagues at faculty level. Data were collected from 519 academics from all IPTA, IPTS, in Malaysia during AKEPT Teaching and Learning training within 2008 to 2009. The study found only three out of ten elements of knowledge dissemination processes show a significant level ( more follow-up after training p= 0.037, supervisor involve me after training p= 0.27 and more confident after training p= 0.037). Where another finding show that another seven elements of knowledge dissemination processes somewhat have less change (asking questions, suggest ides in T&L, involve peers, making a decisions, hold group meeting, taking more time to transform planned into implementation and takes time to reflect). All element are moderately practiced by lecturer at MoHE. As conclusion, this paper raises awareness and provides initial guidelines to the AKEPT’s as training centre for all lecturers to improve knowledge dissemination strategies in their local university. In suggestion, intensive organizations in formulating strategies on how to properly implement and manage their pedagogical knowledge dissemination processes are open to be explore. This study has extended in pedagogical knowledge dissemination for it is probably the first to provide a comparative analysis between AKEPT’s Training Centre and local teaching and learning training centre. It further opens up new lines of future research possibilities. Keywords: knowledge dissemination processes, pedagogical knowledge, perceive competence, training